The Ethical Considerations of Using Gen AI and AI Tools in Academic Writing in Higher Education: A Systematic Review - Sharma , Madhukar (Kalika Journal of Multidisciplinary Research, 2025)
This systematic review investigates the ethical challenges and strategic responses surrounding the use of Generative AI (GenAI) and related tools in academic writing within global higher education. Following the PRISMA 2020 framework, a rigorous search and screening process across academic databases identified 18 peer-reviewed articles published between 2020 and 2025, which were subjected to in-depth thematic analysis. The findings reveal four major ethical concerns: threats to academic integrity through plagiarism, authorship misrepresentation, and diminished originality; issues of bias and fairness arising from algorithmic limitations and unequal access to technology; limited transparency due to nondisclosure of AI use and the absence of clear citation standards; and risks to data privacy linked to the use of student and proprietary information. In response, the literature highlights strategies that include the development of institutional ethical guidelines and policies, enhanced digital literacy and training for faculty and students, improved design and regulation of AI tools with embedded ethical safeguards, and the promotion of transparent human–AI collaboration guided by human oversight. This review demonstrates the significance of adopting a comprehensive, multi-layered approach rather than relying on isolated interventions. For educators, it underscores the need to cultivate critical digital literacy skills; for policymakers, it emphasizes the importance of enforceable and context-sensitive frameworks; and for researchers, it points to future inquiry on the ethical–technological nexus. Collectively, the findings provide actionable insights to ensure that GenAI’s integration into academic writing supports integrity, fairness, and trust in higher education.